The Influence of School Principals’ Managerial Skills on the Quality of Junior High Schools - Dian Nur Afiah; Rasiman Rasiman; Sumarno Sumarno (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to investigate the influence of school principals' managerial skills on the quality of Junior High Schools in Kedungwuni District, Pekalongan Regency. The research used a quantitative approach with a descriptive design, involving 110 teachers from various schools in the district. Data was collected using questionnaires with a Likert scale, and the analysis was performed using simple linear regression analysis. The findings indicate that school principals' managerial skills significantly influence school quality, contributing 61.7% to its improvement. The study further identified that the most significant dimension of managerial skills was human relations, followed by conceptual skills and technical skills. Based on these findings, it is recommended that school principals enhance their managerial skills, especially in technical aspects. Additionally, the local education authority should provide support in developing school principals' leadership capabilities. This study contributes to understanding how effective leadership can significantly improve school quality, offering valuable insights for educational policymakers and practitioners.